2006
DOI: 10.1037/0882-7974.21.2.333
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting the use of technology: Findings from the center for research and education on aging and technology enhancement (create).

Abstract: The successful adoption of technology is becoming increasingly important to functional independence. The present article reports findings from the Center for Research and Education on Aging and Technology Enhancement (CREATE) on the use of technology among community-dwelling adults. The sample included 1,204 individuals ranging in age from 18-91 years. All participants completed a battery that included measures of demographic characteristics, self-rated health, experience with technology, attitudes toward comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

81
962
5
26

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 1,590 publications
(1,131 citation statements)
references
References 57 publications
81
962
5
26
Order By: Relevance
“…Among individuals who are older or in ill health, many refrain from using eHealth technology because of distrust, discomfort, or lack of knowledge. 36,[45][46][47] Even among the technology users in this study, individuals reported a wide range of eHealth literacy levels and frequency of technology use. However, use of online resources is steadily increasing among older adults, 48,49 and once online, individuals who have MCCs or who are in poor health are more likely to use health-related resources.…”
Section: Discussionmentioning
confidence: 99%
“…Among individuals who are older or in ill health, many refrain from using eHealth technology because of distrust, discomfort, or lack of knowledge. 36,[45][46][47] Even among the technology users in this study, individuals reported a wide range of eHealth literacy levels and frequency of technology use. However, use of online resources is steadily increasing among older adults, 48,49 and once online, individuals who have MCCs or who are in poor health are more likely to use health-related resources.…”
Section: Discussionmentioning
confidence: 99%
“…However, older adults are often less successful than their younger counterparts in using technology (e.g., Charness, Schumann, & Boritz, 1992;Czaja et al, 2006;Czaja, Sharit, Ownby, Roth, & Nair, 2001;Kelley & Charness, 1995). This may be due, at least in part, to age-related changes in cognitive abilities that are required by current systems for successful task performance.…”
Section: Discussionmentioning
confidence: 99%
“…On the first day, participants completed a core battery that assessed perceptual speed, working memory, long term memory, verbal ability, reasoning, and spatial abilities as well as a hearing and vision screening (see Czaja, Charness, Fisk, Hertzog, Nair, Rogers, & Sharit, 2006 for details of the protocol). For the present analysis, the ability measures of interest were working memory (alphabet span; Craik, 1986), attention (trail making test; Reitan, 1958), and spatial abilities (paper folding and cube comparison; Ekstrom, French, Harman, & Dermen, 1976).…”
Section: Methods Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Papers were also identified (GonzĂĄlez, RamĂ­rez, & Viadel, 2015), (Cimperman & et al, 2016) that concluded a insignificant or neutral influence of education level upon the elders' acceptance for digital technologies, declaring that even older people with a low level of education modify their attitudes positively toward new technologies when they are motivated by application (learning, connecting to others, entertainment). The reason for this influence would lie not in the specific skills of using the technology (that were not delivered in school long before) but in the development of so called "crystallized intelligence" (Czaja & et al, 2006), wich level is determined by the initial education level and has the ability to strongly diminish the negative atitude towards technology (computer anxiety).…”
Section: Influence Of Education Level On Elderly Acceptance Of Digitamentioning
confidence: 99%